Software Quality 4th International Conference, SWQD 2012, Vienna, Austria, January 17-19, 2012, Proceedings - Biffl, Stefan; Winkler, Dietmar; Bergsmann, Johannes; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the refereed proceedings of the 4th Software Quality Days Conference (SWQD) held in Vienna, Austria, in January 2012.The selection of presentations at the conference encompasses a mixture of practical presentations and scientific papers covering new research topics. The seven scientific full papers accepted for SWQD were each peer-reviewed by three or more reviewers and selected out of 18 high-quality submissions. Further, six short papers on promising research directions were also presented and included in order to spark discussions between researchers and practitioners. The papers are organized into topical sections on software product quality; software engineering processes; software process improvement; component-based architectures; risk management; and quality assurance and collaboration.
Keywords: Software engineering; Management information systems; Computer science; Project management; Software Engineering; Management of Computing and Information Systems; Project Management